2004
DOI: 10.1590/s1516-89132004000200020
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation on heavy metal concentrations in the bivalve Perna perna (LINNAEUS, 1758) on the northern coast of Rio de Janeiro State, Brazil

Abstract: Heavy metal (Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 17 publications
(20 reference statements)
1
21
0
1
Order By: Relevance
“…(Carvalho et al, 2001), and for Cr, Fe, Mn, Pb, and Zn (Carvalho et al, 2001;Ferreira et al, 2004). The present work also corroborates the high concentrations of Cd and Ni (Ferreira et al, 2004), and Zn (Francioni et al, 2004), observed in female mussels of P. perna.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…(Carvalho et al, 2001), and for Cr, Fe, Mn, Pb, and Zn (Carvalho et al, 2001;Ferreira et al, 2004). The present work also corroborates the high concentrations of Cd and Ni (Ferreira et al, 2004), and Zn (Francioni et al, 2004), observed in female mussels of P. perna.…”
Section: Resultssupporting
confidence: 88%
“…Interferences of seasonality on the bioaccumulation of trace metals in P. perna mussels may have different profiles depending on the study region and survey period. Ferreira et al (2004), when evaluating P. perna mussels in three beaches in the northern coast of Rio de Janeiro, did not find a seasonal trend of accumulation.…”
Section: Resultsmentioning
confidence: 71%
“…Verificou-se que os valores de N, K, Cr e MPI 1 não diferiram sazonalmente (p > 0,05). As concentrações dos metais pesados Cu, Fe, Mn, Zn, Cd e Pb, tanto na primavera quanto no verão, foram superiores (p < 0,01) ao outono e inverno, diferindo dos resultados apresentados por outros autores 25 que, ao descreverem as concentrações de Cd, Cr, Cu, Fe, Mn, Ni, Pb e Zn em Perna perna de três praias na costa Norte do estado do Rio de Janeiro, não encontraram tendência sazonal de acumulação. Os metais Cd, Pb e Cr, independente da estação do ano ou do ponto de coleta do mexilhão na área aquícola, encontram-se em uma concentração muito superior àquela estipulada pela ANVISA.…”
Section: Resultsunclassified
“…These seasonal variations have been related to a great extent to seasonal changes in flesh weight during development of gonadic tissues [18,[25][26][27]. Variability of Paradoxa (Born 1778) from the Volta Estuary, Ghana heavy metal concentrations can also be caused by changes in the physiological conditions of the clams [28,29] and environmental parameters including temperature, pH, salinity, oxygen concentrations [30,31]. Except Hg, all the metals examined in this study are essential for clams and have intracellular regulatory mechanisms [32] to keep their concentrations in the clam tissues in equilibrium.…”
Section: Discussionmentioning
confidence: 99%